Genetic testing in children and young people. - Parker, M (2010)
Guidelines on childhood genetic testing are in broad agreement that where there are no 'urgent medical reasons', presymptomatic and predictive testing for adult-onset disorders, and carrier testing should be postponed until a child is able to give his or her own consent, either as a competent young person, or as an adult. This paper explores situations in which this requirement can be in tension with genetics professionals' and others' judgement of what is in the child's best interests. It concludes that whilst the guidelines do reflect a broad agreement that in most cases testing children for adult onset conditions or carrier status is inappropriate, there are at least some situations in which testing may be thought by genetics professionals to be appropriate. Many of the morally relevant features of such cases will often be context specific, i.e. to do with the child's family and other relationships or other features of the local context and this suggests that any revision of the guidelines on genetics testing in childhood will need to take into account the need to allow space for the utilisation of judgement by genetics professionals about whether genetic testing is in the child's best interests. In making such judgements the genetics professional will need to pay close attention to the views of the child's parents and do all they can to facilitate input from the child him or herself.